Non-thermal plasma induces immunogenic cell death in vivo in murine CT26 colorectal tumors. (2nd September 2018) - Lin, Abraham G.; Xiang, Bo; Merlino, Dante J.; Baybutt, Trevor R.; Sahu, Joya; Fridman, Alexander; Snook, Adam E.; Miller, Vandana
ABSTRACT: Immunogenic cell death is characterized by the emission of danger signals that facilitate activation of an adaptive immune response against dead-cell antigens. In the case of cancer therapy, tumor cells undergoing immunogenic death promote cancer-specific immunity. Identification, characterization, and optimization of stimuli that induce immunogenic cancer cell death has tremendous potential to improve the outcomes of cancer therapy. In this study, we show that non-thermal, atmospheric pressure plasma can be operated to induce immunogenic cell death in an animal model of colorectal cancer. In vitro, plasma treatment of CT26 colorectal cancer cells induced the release of classic danger signals. Treated cells were used to create a whole-cell vaccine which elicited protective immunity in the CT26 tumor mouse model. Moreover, plasma treatment of subcutaneous tumors elicited emission of danger signals and recruitment of antigen presenting cells into tumors. An increase in T cell responses targeting the colorectal cancer-specific antigen guanylyl cyclase C (GUCY2C) were also observed. This study provides the first evidence that non-thermal plasma is a bone fide inducer of immunogenic cell death and highlights its potential for clinical translation for cancer immunotherapy.